Influence of deterministic stresses on flow prediction of a low-speed axial flow compressor rear stage. - Li, Y. G.; Tourlidakis, A. (Professional Engineering Publishing, 2001)
Deterministic stresses are used to describe the unsteady effects on the flow field in multistage axial flow compressors. In this paper, a circumferentially non-uniform mixing plane method implemented with deterministic stresses is used for the flow prediction inside the rear stage of an axial flow compressor in a multistage environment. The deterministic stress field is calculated with an overlapped solution approach for the same flow passage and implemented with the Navier-Stokes equations in order to provide continuous interfaces. The aerodynamic boundary condition is simplified with the application of a repeating stage model where only the mass flowrate and stage exit average static pressure are required. Two computational cases for the third stage of the Cranfield low-speed research compressor, one with the mixing plane model and the second with the mixing plane model in combination with deterministic stresses, are examined and compared with each other and also with corresponding experimental data. It is shown that the implementation of the deterministic stresses is beneficial for the flow prediction but the improvement in accuracy for low-speed axial flow compressor rear stages is not significant.